Living Graffiti, Living the City: Porto inhabitants’ social representations of graffiti art pieces - de la Torre, Elena; Ferro, Ligia (Revista de Ciências Sociais, 2016)
We try to analyze the representations of different graffi ti pieces located in the city of Porto, Portugal, focusing the city dwellers’ perspective. Graffi ti has been approached from diverse disciplinary points of view and frequently from the lenses of its protagonists. For that reason, it is considered that it is required to analyze the way by which others, the ones that ignore the style and symbolic codes of graffi ti production, think and envision graffi ti in the urban space and how they think the city through it. We used the photovoice technique to collect testimonies and the result was a plurality of visions on the images at stake.